The Evolution of the Campus Novel: From Tradition to Postmodernism - Mahliyo ORTIQOVA (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
The campus novel, as a genre of academic fiction, represents an evolving reflection of intellectual culture and academic life. It portrays universities as microcosms of broader society, exposing tensions between knowledge, power, and morality. This paper explores the development of the campus novel from its traditional British origins in the mid-twentieth century to its postmodern reinterpretations. By examining the works of Kingsley Amis, C. P. Snow, David Lodge, and Malcolm Bradbury, the study reveals how the genre transitioned from realist satire to metafictional and poststructuralist explorations of academic discourse. The analysis also considers how contemporary writers continue to redefine the genre in an age of globalization and digital transformation.